Pengaruh Penggunaan Media Sosial dan Berkomunikasi Interpersonal Terhadap Kinerja Pegawai dengan Teknologi Informasi sebagai Mediasi pada Sekretariat Daerah Kabupaten Pati - Catur Novitasari; Ahmad mardalis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to analyze the effect of Social Media Use, Interpersonal Communication on Employee Performance with Information Technology as a mediator at the Pati Regency Regional Secretariat. The population of this study were all employees of the Pati Regency Regional Secretariat office with a sample used in this study totaling 116 respondents adjusted to the results of the calculation according to the number of question indicators. This study is a quantitative study using data sources, namely primary data obtained by filling out questionnaires distributed directly by researchers. The analysis tool used is SmartPLS. The results of this study indicate that 1.) there is a negative and insignificant effect of social media use on employee performance, while there is a positive and significant effect of social media use on information technology 2.) there is a positive and significant effect of interpersonal communication on information technology and employee performance variables 3.) information technology variables are able to mediate the use of social media on employee performance and mediate interpersonal communication on employee performance with positive and significant results.